Application of Integrated Quality Management Transformational Studies in Higher Education - Alvi Razanah; Nanda Indah Putri; Masduki Asbari (Universitas Muhammadiyah Enrekang, 2022)
With the implementation of integrated education quality management, the quality of national education education standards will be achieved. A quality management system that is implemented with a consistent commitment will provide benefits and success for all stakeholders in higher education institutions. So to achieve this benefit and success, it must be based on several established quality management principles. Starting the entry of foreign universities to enliven the